"Healthier Choice” Logo (BPOM) Education on Knowledge and Selection of Processed Food Products for Public Health IIK STRADA Student’s - Fenita Indriani; Muhammad Ali Sodik; Amarin Yudhana (Journal of Hospital Management and Services, 2023)
September 3rd, 2019, the BPOM held a socialization nutritional foods labeling, discussing about ING design regulation, to make consumers easier to understand logo with the “Healthier Choice”. Yet, in previous studies, Indonesian people are still not aware to the nutritional composition (BPKN, 2013). The purpose of this study is to analyze the effect of education BPOM "Healthier Choice" logo against people awareness of processed food products and selection of the product itself. The design of this study is pre-experimental involving one group of pretest - posttest. The population are 62 students of the Public Health IIK Strada, with 54 students as sample. The sampling technique used is stratified random sampling. The dependent variable in this study is knowledge and product selection. Data were obtained from questionnaires and processed by Wilcoxon statistic test From the results of the study, that p-value = 0.000 (p <0.05) which mean there was an effect of "Healthier Choice" logo BPOM education on the product knowledge and product selection of food in the Public Health IIK STRADA student’s. In line with Notoatmodjo's (2010) theory that knowledge is the result of human sensing of an object through the five senses involving the senses of sight, hearing, taste and smell of an object which is also influenced by the intensity of perception. Most of human knowledge is obtained through the eyes and ears. Furthermore, according to Contento (2011), nutrition education will affect the factors that influence food selection so as to form appropriate food choices and eating habits.